Mathematical Modeling of the Resistance of Pulling out Steel Bars from High Strength Concrete - Babych, Yevgenij; Filipchuk, Sergij; Fenko, Oleksiy (International Journal of Engineering and Technology, 2018)
The article gives the results of the experimental researches of the bond between steel and high strength concrete. According to these results the mathematical model was built to define the boundary stresses of the bond between steel and concrete on their contact surface. The analysis of the impact of the specific factors on the boundary stresses of the bond between steel and concrete was carried out.Â